STRATEGI BERSAING BIRO PERJALANAN WISATA ALINDO DEWATA TOURS BALI - Lintong, Nelsye Natalina (JURNAL MASTER PARIWISATA; Volume 02, Nomor 01, Juli 2015DO - 10.24843/JUMPA.2015.v02.i01.p07)
Alindo Dewata Tours Bali as an inbound tours companydeals with the competitors by applying competitive strategy.Nevertheless the competitive strategy applied is not maximumyet. It is apparently seen at the average growth of touristsnumber handled since 2004-2013 by the company only 5,97 %.Therefore, this study has the objective to know what internalexternal factors that give influences and competitive strategy tobe applied in the company. This research using analysis toolsof Internal Factor Evaluation (IFE) matrix, External FactorEvaluation (EFE) matrix for general strategy, Internal External(IE) matrix, Strength Weakness Opportunity Threat (SWOT)matrix for alternative strategy and Quantitative StrategicPlanning Matrix (QSPM) for priority strategy. The result of IFEmatrix indicates bundle pricing policy as the prime strengthand the application of the management information system notmaximum as the prime weakness. EFE matrix indicates qualitystrategy contributes the service as prime opportunity and thedependency on the foreign travel agencies as prime threat.Based on IE matrix, the company’s position is at five (V) levelfor resistance and endurance strategy. SWOT matrix indicateseight competitive strategic alternatives. Suggested first priorityby QSPM is to develop market segment, both overseas anddomestic market.
Keywords: Competitive strategy, inbound tours, industrialorganization, resource-based view